Relationship of Patterns of Giving Solid Food Based on Zero Waste with the Incidence of Anemia in Infants - Anur Rohmin; Ni Nyoman Deni Witari; Ainal Mardiah; Nurul Amalina; Septi Viantri Kurdaningsih (Bulletin of Inspiring Developments and Achievements in Midwifery, 2026)
Background: Anemia in infants remains a significant public health problem in Indonesia, contributing to impaired growth, cognitive development, and reduced immunity. Inappropriate complementary feeding (MPASI) practices, including limited implementation of environmentally friendly (zero-waste) approaches, may negatively affect infant nutritional status. Objective: To analyze the relationship between zero-waste complementary feeding practices and anemia among infants aged 6–12 months at Situjuh Primary Health Center, Lima Puluh Kota. Methods: A quantitative cross-sectional study was conducted among 75 infants selected through purposive sampling. Data on complementary feeding practices were collected using structured interviews, while anemia status was determined by measuring capillary blood hemoglobin levels. Data were analyzed using the chi-square test. Results: Among the participants, 64% received zero-waste complementary feeding, and the prevalence of anemia was 32%. A significant association was found between zero-waste complementary feeding and anemia incidence (p = 0.015). Infants receiving environmentally friendly complementary feeding had a lower risk of anemia than those with conventional feeding practices (OR = 0.45; 95% CI: 0.21–0.93). Conclusion: Zero-waste complementary feeding is associated with a reduced risk of anemia in infants. Promoting environmentally friendly complementary feeding practices may help prevent anemia while supporting optimal infant nutrition and environmental sustainability.